ENDOTHELIN INTERMEDIAETES BY ASYMMETRIC CONJUGATE ADDITION REACTION USING A CHIRAL ADDITIVE - TILLYER, RICHARD D; TSCHAEN, DAVID M; XU, FENG (2002)
This invention relates to a process for the preparation of a key intermediate in the synthesis of an endothelin antagonist, having formula (I) by using a chiral additive to effect an asymmetric conjugate addition. Ovaj pronalazak se odnosi na postupak za dobijanje ključnog intermedijara u sintezi endotelin antagonista, koji ima formulu (I) upotrebljavajući hiralni aditiv da bi se ostvarila asimetrična konjugovana adicija.[This invention relates to a process for the preparation of a key intermediate in the synthesis of an endothelin antagonist, having formula (I) by using a chiral additive to effect an asymmetric conjugate addition.